Quillaja saponaria bark saponin attenuates methotrexate induced hepatic oxidative stress, inflammation and associated liver injury in rats - Mustafa Ahmed Abdel-Reheim, Ahmed Amine Ashour, Mohamed Abdelrazik Khattab, Ahmed Gaafar A. Gaafar (Journal of Applied Pharmaceutical Science, 2022)
Quillaja saponaria Molina tree bark represents the main source of Q. saponaria saponin that has antitussive-, antiinflammatory-, and immune-stimulant effects. In spite of such multiple applications, the potential role of Q. saponaria bark saponin (QBS) as a hepatoprotective agent has not been elucidated. On the other hand, methotrexate (MTX) is an antineoplastic/immunosuppressive drug that may cause serious liver complications which limit its clinical use as a result of the arising oxidative stress, inflammation, and apoptosis. This study aimed to investigate the protective effects of QBS against MTX-induced hepatotoxicity. Thirty-two male rats were divided into four groups (N = 8). Control rats received oral saline (0.2 ml/day, for 10 days) (group I). In group II, rats were administered oral saponin (100 mg/kg/day, for 10 days). In group III, rats received saline (0.2 ml/day, p.o., for 10 days) and then were injected with single i.p. MTX (20 mg/kg) on day 5. Rats in group IV (MTX + QBS) received saponin (100 mg/kg/day, p.o., for 10 days) with single i.p. MTX (20 mg/kg) on day 5. On day 11, blood and livers were collected. Serum alanine aminotransferase (ALT), serum aspartate aminotransferase (AST), serum alkaline phosphatase (ALP), and serum lactate dehydrogenase (LDH) levels were measured as liver-damage biomarkers. Hepatic malondialdehyde (MDA), reduced glutathione (GSH), and total nitric oxide content (NOx ) were determined as oxidative-stress measures. Hepatic Bcl-2 and Bcl-2 associated-X-proapoptotic protein (Bax) mRNAs were assessed as apoptosis biomarkers. Hepatic nuclear factor erythroid 2-related factor-(Nrf-2)/heme oxygenase-1 (HO-1) immunoreactivities were evaluated as indicators for inflammation. Interestingly, QBS attenuated MTX-mediated elevations of AST, ALT, ALP, LDH, MDA, NOx , and Bax, while inhibiting MTX-induced decreases in GSH, Nrf-2, HO-1, and Bcl-2. Histological analysis further confirmed the hepatoprotective microenvironment rendered by QBS. Conclusively, our findings represent the first evidence that QBS might confer valuable hepatoprotection against MTX-mediated liver damage through suppression of oxidative stress, apoptosis, and amelioration of tissue inflammation, proposing QBS as an effective therapeutic regimen to be involved in future hepatic-support therapies.
Keywords: Quillaja saponaria, methotrexate, hepatotoxicity, oxidative stress, apoptosis, Nrf-2/HO-1